Analisis Visual Rumah Kelahiran Dan Peninggalan Tan Malaka Di Pandam Gadang, Gunuang Omeh, Kabupaten Lima Puluh Kota (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
Tan Malaka was one of the most famous revolutionary figures during the Indonesian independence movement. His birth house is one of the heritage objects in Nagari Pandam Gadang, Gunuang Omeh, Lima Puluh Kota Regency which was established around the 1860s before Tan Malaka was born. However, over time, Tan Malaka's birth house has become increasingly neglected. The unclear management of this house is one of the factors that affect it. Seeing this condition, the researcher raised Tan Malaka's birth house as an object of research in the author's scientific work. The type of research method used is descriptive qualitative research method. This research produces descriptive data in the form of images and visual analysis of the relics found in the Tan Malaka House. This research is intended to revive the interest and appreciation of the community, especially West Sumatra residents, for the role of Tan Malaka's house as part of the history of Indonesian heroes so that it can continue to inspire and provide valuable insights for the future.